Semicontinuity of Solution Mappings to Parametric Generalized Vector Equilibrium Problems. (1st November 2016) - Han, Yu; Gong, Xunhua
ABSTRACT: In this article, stability results concerning the lower semicontinuity and the Hausdorff upper semicontinuity of the solution mappings to parametric generalized vector equilibrium problems with neither the monotonicity of mappings nor any information of the solution mappings are established by using scalarization methods and a new density result.